The Existence of Hadroh within the Dynamics of Islamic Civilization: A Literature Analysis of the Role of Art as a Medium for Da'wah and Character Education - Rifdah Arifah; Haura Nida Hanifah P.R; Aidil Fazlur Rahman Nasution; Saiful Ramadhan; Abdul Fadhil (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2026)
Hadroh is an Islamic art form originating from the Middle Eastern religious musical tradition and developing as part of Islamic culture in Indonesia. Besides being a form of religious entertainment, Hadroh also serves as a medium for da'wah (Islamic outreach) and character education, embodying religious values, discipline, responsibility, and social solidarity. In the era of globalization and the development of digital technology, Hadroh's existence faces challenges from global popular culture, which is widely sought after by the younger generation. This study aims to analyze Hadroh's role as a contemporary da'wah medium and a means of character education through a literature review. Data were obtained from scientific journal articles from 2020–2026 accessed through Google Scholar and Sinta, then analyzed using content analysis methods. The results show that Hadroh has strong historical roots in Islamic civilization and is able to adapt to current developments through digital media. Furthermore, Hadroh activities are considered effective in instilling character values ​​in the younger generation through an artistic and cultural approach. Thus, Hadroh continues to exist as a relevant Islamic cultural heritage in strengthening the religious identity of young Indonesian Muslims.